O‘ZBEKISTON RESPUBLIKASIDA QO‘SHILGAN QIYMAT SOLIG‘INING BUDJET DAROMADLARIDAGI YIRIK MANBAI SIFATIDAGI ROLINI BAHOLASH - Po‘latov , Sherzodbek Oybek o‘g‘li (Innovative Development in Educational Activities, 2023)
In this article, the role of the value added tax in the budget revenues in Uzbekistan. Analytical opinions on the increase of revenues to the budget of the indirect tax through the budget-tax policy are expressed. Also, the value added tax The results of the statistical analysis about the negative consequences of the interruption of the supply chain, as well as the fact that the budget does not reach the budget on time, have been shown.